2015
DOI: 10.1590/0103-8478cr20141082
|View full text |Cite
|
Sign up to set email alerts
|

Plant vibration of american pepper cultivars for fruit production in protected environment with and without closed sides

Abstract: The aim of this research was to evaluate plant vibration for fruit and seed production of american pepper in greenhouse with open and closed sides. The experiment was carried out at Fazenda Experimental da Unesp

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In these confines pollination is enhanced with manually vibration of each plant by hand (Freitas et al . ), vibration from a supporting structure (Short & Bauerle ) through the use of vibrating wands (Massa et al . ), vibrating tables or air blast devices that promote pollination as anthers dehisce.…”
Section: Fruit Without Pollinatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these confines pollination is enhanced with manually vibration of each plant by hand (Freitas et al . ), vibration from a supporting structure (Short & Bauerle ) through the use of vibrating wands (Massa et al . ), vibrating tables or air blast devices that promote pollination as anthers dehisce.…”
Section: Fruit Without Pollinatorsmentioning
confidence: 99%
“…Techniques have been defined for greenhouses and extra-terrestrial environments where bees are not an option (Schubert 2017). In these confines pollination is enhanced with manually vibration of each plant by hand (Freitas et al 2015), vibration from a supporting structure (Short & Bauerle 1973) through the use of vibrating wands (Massa et al 2015), vibrating tables or air blast devices that promote pollination as anthers dehisce. Selection of specific flower types may enhance amenability to mechanical, non-insect pollination.…”
Section: Fruit Without Pollinatorsmentioning
confidence: 99%
“…Other studies investigating tomatoes and eggplants (also buzz-pollinated) also found that tapping of the trellis wires improved fruit set and seed number compared with untreated plants, however the effects were significantly inferior compared with bee pollinated trials [79,80]. Conversely, studies using other Solanaceae crops (eggplants and sweet peppers) found no significant effect of trellis tapping on seed set and fruit weight, across multiple cultivars and treatment groups (e.g., untreated plants, and indoor and outdoor grown crops) [72,81]. The efficacy of the technique seems to vary across cultivars and growth environments, with different costs to the industry (Table 2).…”
Section: Mechanical and Other Artificial Pollination Strategiesmentioning
confidence: 99%
“…Vibrating probes can be used to oscillate the staminal cone to elicit pollen expulsion (Figure 7) [20]. Artificial vibrations of individual inflorescences have been reported to increase fruit weights by 10-17% in open field systems [72] and overall fruit yield by 75% in greenhouse production [25], when compared with non-treated controls. Electric toothbrushes (Figure 7) have also been reported to achieve comparable results to tuning fork treatments, noting that the effect of frequency on pollination outcomes was negligible but was more dependent on the buzzing duration and plant species [73].…”
Section: Mechanical and Other Artificial Pollination Strategiesmentioning
confidence: 99%